Ni12 tetracubane cores with slow relaxation of magnetization and efficient charge utilization for photocatalytic hydrogen evolution. Issue 45 (10th November 2022) - Tanuhadi, Elias; Cano, Joan; Batool, Samar; Cherevan, Alexey; Eder, Dominik; Rompel, Annette
Abstract : Two Ni12 -multicubane topologies Ni12 W30 and Ni12 W27 have been synthesized. Magnetometry and homogeneous catalytic studies probing their properties as hydrogen evolution photocatalysts clearly distinguish Ni12 W30 and Ni12 W27 from Ni4 cubanes. Abstract : We report two Ni12 multicubane topologies enclosed in the polyanions [Ni12 (OH)9 (WO4 )3 (PO4 )(B-α-PW9 O34 )3 ] 21− Ni12 W30 and [Ni12 (OH)9 (HPO4 )3 (PO4 )(B-α-PW9 O34 )(A-α-PW9 O34 )2 ] 21− Ni12 W27 that magnetically behave as Ni12 units clearly distinguishing them from typical Ni4 cubanes as shown by magnetic studies together with high field and frequency electron paramagnetic resonance (HFEPR). Beyond the unprecedented static properties, Ni12 W30 shows the unusual coexistence of slow relaxation of the magnetization and a diamagnetic ground state ( S = 0), providing the unique opportunity of studying the essentially elusive magnetic relaxation behavior in excited states. The cubane-topology dependent activity of Ni12 W30 and Ni12 W27 as homogeneous HER photocatalysts unveils the structural key features significant for the design of photocatalysts with efficient charge utilization exemplified by high quantum yields (QY) of 10.42% and 8.36% for Ni12 W30 and Ni12 W27 , respectively.